(untitled) (Global Economic Review: Journal of Economics, Policy, and Business Development, 2026)
The article examines the prospects for foreign banks entering the market of Uzbekistan, the problems that exist for foreign banks, and how the legislation of the Republic of Uzbekistan creates a framework for attracting foreign capital to the country’s market. In addition, the factors influencing the possibility of foreign banks entering the country’s market are analyzed.